2013
DOI: 10.1042/cs20120470
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant treatment prevents the development of fructose-induced abdominal adipose tissue dysfunction

Abstract: In the present study, we tested the effect of OS (oxidative stress) inhibition in rats fed on an FRD [fructose-rich diet; 10% (w/v) in drinking water] for 3 weeks. Normal adult male rats received a standard CD (commercial diet) or an FRD without or with an inhibitor of NADPH oxidase, APO (apocynin; 5 mM in drinking water; CD-APO and FRD-APO). We thereafter measured plasma OS and metabolic-endocrine markers, AAT (abdominal adipose tissue) mass and cell size, FA (fatty acid) composition (content and release), OS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 53 publications
2
30
0
5
Order By: Relevance
“…Bcl-2 has been well known as an effective anti-apoptotic factor, leading to Bax inactivation and reliving mitochondria. However, Bcl-2 function loss is a major cause for Caspase-3 activation, resulting in apoptosis [41]. These results above in vivo indicated that quercetin showed effects on enhancing AKT activity.…”
Section: Discussionmentioning
confidence: 95%
“…Bcl-2 has been well known as an effective anti-apoptotic factor, leading to Bax inactivation and reliving mitochondria. However, Bcl-2 function loss is a major cause for Caspase-3 activation, resulting in apoptosis [41]. These results above in vivo indicated that quercetin showed effects on enhancing AKT activity.…”
Section: Discussionmentioning
confidence: 95%
“…We still do not know the precise mechanism that triggers this pro-/anti-adipogenic balance in FRD rats. It is tempting to speculate that the general oxidative stress (TBARS) and local oxidative stress (VAT) [3] present in FRD animals could be one such trigger. This state of FRD-induced high oxidative stress could in turn decrease sirtuin-1 production [25], a NAD + -dependent histone deacetylase that represses PPARc expression [26] and thus inhibits adipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In these animals, we also recorded a marked increase in visceral adipose tissue (VAT) mass and impairment of its metabolic and endocrine functions [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations